Editorial: Aspiration management and rehabilitation - Palmer, Phyllis M.; Leslie, Paula (Frontiers in Rehabilitation Sciences, 2025)
Clinical management of prandial aspiration remains heavily influenced by long-standing practices and may not align with current evidence. This editorial provides a broad overview of the articles in this edition of Frontiers in Rehabilitation Sciences and addresses three common misconceptions in dysphagia management: (a) that prandial aspiration always requires immediate restrictive intervention, (b) that coughing during meals indicates physiologic dysfunction, and (c) that thickened liquids universally reduce aspiration risk without consequence. We examine how these myths conflict with current evidence and highlight supportive perspectives from various disciplines. Rather than introducing new techniques, we encourage critical examination of current practices and provide guidance for implementing evidence-supported interventions. The goal is to move toward individualized care that considers multiple risk factors beyond the mere presence of aspiration, ultimately improving patient outcomes while maintaining quality of life.